2021
DOI: 10.2147/jmdh.s309020
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Nurses’ Perception of Antibiotic Use and Resistance: A Qualitative Inquiry

Abstract: Purpose Quality use of antibiotics and the development of antibiotic resistance is a global catastrophe. In the conceptual context, the phenomenon is correlated with the healthcare practitioners’ understanding of antibiotic use and resistance. Therefore, the study aimed to highlight nurses’ perception of antibiotic use and resistance at a public healthcare institute in Quetta City, Pakistan. Respondents and Methods By using a semi-structured interview guide through the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Multiple studies reported a widespread shortage of medical infrastructure, equipment, and personnel across diverse settings, resulting in poor access to laboratory testing and diagnostics. In urban settings, there is a shortage of hospital personnel paired with a high volume of patients, leading to the prescription of common antimicrobial regimens without in-depth assessment of patients or laboratory testing [ 82 , 88 , 95 , 99 , 102 , 103 ]. Additionally, physicians are often unavailable or there are long wait times, prompting individuals to obtain antimicrobials on their own rather than access these formal facilities [ 28 , 66 , 77 , 84 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies reported a widespread shortage of medical infrastructure, equipment, and personnel across diverse settings, resulting in poor access to laboratory testing and diagnostics. In urban settings, there is a shortage of hospital personnel paired with a high volume of patients, leading to the prescription of common antimicrobial regimens without in-depth assessment of patients or laboratory testing [ 82 , 88 , 95 , 99 , 102 , 103 ]. Additionally, physicians are often unavailable or there are long wait times, prompting individuals to obtain antimicrobials on their own rather than access these formal facilities [ 28 , 66 , 77 , 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…receiving an antimicrobial prescription because they believe it will successfully treat their children, elders, and other vulnerable groups [81,86]. The high value placed on antimicrobials and belief in their power leads patients to expect and even demand antimicrobials when seeking medical care [87][88][89]. Patients will "doctor shop" or seek care only from providers who are known to readily provide antimicrobials or pharmacies that are liberal with their distribution [65,[90][91][92].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…Additionally, caregivers report feeling a sense of emotional relief receiving an antimicrobial prescription because they believe it will successfully treat their children, elders, and other vulnerable groups (81,86). The high value placed on antimicrobials and belief in their power leads patients to expect and even demand antimicrobials when seeking medical care (87)(88)(89).…”
Section: Individual Level: Patients and Their Caregiversmentioning
confidence: 99%
“…Poor knowledge of the healthcare professionals regarding quality use of antibiotics, lack of antibiotic stewardship programs for healthcare professionals including nurses, self-medication by the general public due to insufficient knowledge and financial crisis especially in the developing countries are the main contributing factors towards the development of antimicrobial resistance. Also, the patients' expectation for antibiotics is another factor influencing physicians' antibiotic prescribing behaviors (Anwar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Among all healthcare professionals, nurses are an integral component of the healthcare system. Nurses have direct interaction with the patients during the drug administration process and play an important role in ensuring quality use of medicines (Anwar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%